2001
DOI: 10.1016/s0893-133x(01)00325-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Total Sleep Deprivation on Cerebral Responses to Cognitive Performance

Abstract: We review the findings from a study utilizing functional magnetic resonance imaging (FMRI) Understanding the impact of sleep deprivation on cognitive performance is increasingly important in a society where many people acutely or chronically fail to obtain adequate sleep. Recent advances in functional brain imaging techniques allow researchers to relate brain function more directly than ever to behavioral performance following sleep deprivation. Prior to our study described below, only three published neuroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
153
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(175 citation statements)
references
References 20 publications
15
153
0
5
Order By: Relevance
“…reversed the effects of sleep deprivation on CMRglc levels in the thalamus (Fig. 6), a brain region highly susceptible to sleep deficits in humans (Thomas et al, 2000;Drummond and Brown, 2001;Lambe et al, 2005). The fact that nasal orexin-A was effective in reversing performance on High-load trials, even to a greater extent than in normal alert sessions, suggests that: 1) high cognitive load trials engage either different brain processes or the same processes to a greater extent than low cognitive load trials, and 2) "high load cognitive processes" may recruit many neurons that have orexin receptors that can be activated more effectively by peptide delivery via the nasal route (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…reversed the effects of sleep deprivation on CMRglc levels in the thalamus (Fig. 6), a brain region highly susceptible to sleep deficits in humans (Thomas et al, 2000;Drummond and Brown, 2001;Lambe et al, 2005). The fact that nasal orexin-A was effective in reversing performance on High-load trials, even to a greater extent than in normal alert sessions, suggests that: 1) high cognitive load trials engage either different brain processes or the same processes to a greater extent than low cognitive load trials, and 2) "high load cognitive processes" may recruit many neurons that have orexin receptors that can be activated more effectively by peptide delivery via the nasal route (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The brain areas responsible for cognitive domains that are related to attention and memory include the basal forebrain, hippocampus, prefrontal cortex, and thalamus (Thomas et al, 2000;Portas et al, 1998;Posner et al, 1997;Pigott and Milner, 1993). The prefrontal cortex and thalamus are both proposed to be vulnerable to sleep loss as well, although the influence of sleep deprivation on cerebral activation is not yet clearly defined (Drummond et al, 2004;Drummond and Brown, 2001;Harrison et al, 2000;Thomas et al, 2000;Portas et al, 1998). In addition, the basal forebrain and thalamus belong to the brain areas in which receptors for sex hormones, especially estrogen, are found (McEwen and Alves, 1999;Bixo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recent electro e n c e p h a l o g r a p h i c and neuroimaging studies revealed that the pref rontal cortex (PFC) is more responsive to sleep deprivation then other brain areas 2,[8][9][10][11][12] , which is expected since the frontal region has a greater restorative need than other areas of the brain. In fact, during non-REM sleep, in the rebound sleep after SD, the i n c rease in delta-wave frequency (1-4 Hz, slow wave activity related to deep sleep) occurs first in the PFC and later on other areas of the cort e x 1 3 , 1 4 , suggesti n g the importance of the initial re c o v e ry in this re g i o n .…”
mentioning
confidence: 99%